'I'm classic now': Byron's engagement with antiquity - Caines, K (2018)
Against the background of current debate within the academy about a less rigid demarcation between British Neoclassical and Romantic writing generally, and about the place of Rome among the Romantics specifically, this thesis examines Byron’s engagement with antiquity. It reveals Byron as a sophisticated reader and inventive re-imaginer of classical texts and approaches. A significant component of his literary aesthetic was the extensive, and often highly creative, substratum of classical intertextuality in his writings throughout his life. By contrast, his exploitation of ancient texts as formal models fell largely into two periods, with an intense engagement in his apprentice years until 1812 and again in his artistic maturity from 1818, but a comparative hiatus during his ‘Years of Fame’ when he published Childe Harold’s Pilgrimage and the Oriental tales. His instincts in this regard were not academic or antiquarian. The value of the classical to Byron was not primarily to recover the past, but to illuminate the present and to enrich the reading experience. A key contention of this thesis is that, notwithstanding Byron’s libertarian support of Greek independence from Turkey and a Hellenophilic culture in Britain in the early nineteenth century, his Hellenism—in the sense of being influenced by ancient Greek culture—and his expertise in ancient Greek have in general been over-emphasised. Conversely, the influential role of Latin texts and the Roman world in his self-construction and literary development has been under-appreciated. There is a preponderance of Latin source material in Byron’s classical translations and ‘imitations’, forms largely confined to his early years. Moreover, Roman writers emerge as central to the great works of his maturity in satire, epic and even tragedy, where the thesis argues that the principal classical dramaturgical influences on Byron’s three, professedly Greek, closet dramas of 1820–21—Marino Faliero, Sardanapalus and The Two Foscari—were in fact the tragedies of the contemporaneously unfashionable Roman writer, Seneca. As revealed by his poetry and letters, what is most striking about Byron’s engagement with classical literature, once he left behind the enforced requirements of school and university, is his predominant Latinity.